Pitag’ORA PRO NOBIS - Babini, Stefano; Graziani, Ivan (EDiMaST: Experiences of Teaching with Mathematics, Sciences and Technology, 2016)
“Pitag'ORA PRO NOBIS” comes out from our desire to deal with Pythagoras and the Pythagorean school. We decided to fulfil this project by realizing a workshop in an exciting and unconventional way. We took into account the “Indicazioni Nazionali 2012” with reference respectively to the Pre-school and Primary School curriculum, and to the secondary high school “Assi culturali”. We decided to treat some particularities of the so-called “arithmo-geometry”, introduced by the Pythagoreans, with the study of algebraic numbers and their characteristics, also figured. We then moved on to some examples of demonstrations of the famous theorem, then started to analyze some peculiarities and regularities contained in Pythagorean triples. For these activities we tried to address these nodes in a different and funny way, alternating, at all levels, the mathematical rigor to moments of imagination and games. We tried to make a mathematician like Pythagoras nicer. In fact, He's well-know for his most famous theorem but at the same time he's not loved by most students. For this reason, this experience involved first by the pre-school including children of 5 years, and then all classes of the primary school, then the secondary school and finally the secondary high school